EXPLORING THE FORMATION OF COALITIONS BETWEEN ISLAMIST AND SECULAR PARTIES IN INDONESIA LOCAL ELECTIONS: FIGURE, PATRONAGE AND COMMON ENEMY - Abdul Chalik , Muhaemin Latif (Hamdard Islamicus, 2020)
The issue of difficulties in building coalitions between PKS and PDIP has been widely discussed by the scholars. This paper presents the reasons for the formation of coalition between secular and Islamic parties in supporting the election of leaders where coalitions are formed at the local level. The study suggests that the track record of candidate, patronage system, and the involvement of elites either from inside or outside of the party, determine the treatise of a coalition. In addition, an effort to make the dominant political power as the common enemy is another strategyin the local political contest. The study also found that the coalition of inter ideologies can lead to the creation of temporary coalitions where political interests align